Energy poverty vulnerability index: A multidimensional tool to identify hotspots for local action - Gouveia, João Pedro (2019)
info:eu-repo/grantAgreement/FCT/5876/147274/PT The authors would like to acknowledge the partial funding given to this research by ERSE PPEC 2017–2018 through the project “LIGAR – Eficiência Energética para todos” and to the Portuguese Foundation for Science and Technology through the strategic project grantnumber UID/AMB/04085/2013 which gives financial support to CENSE.